STUDI KASUS : PENERAPAN EVIDENCE BASED PRACTICE PADA PERSALINAN DENGAN KETUBAN PECAH DINI - Hermanses, Sitti Suharni; Kotarumalos, Sitti Sarifah (Jurnal Kebidanan, 2025)
Premature Rupture of Membranes (PROM) is one of the obstetric complications that often causes morbidity and mortality in both mothers and infants. This condition occurs when the amniotic membranes rupture before the onset of labor contractions or before the gestational age reaches 37 weeks. PROM increases the risk of intrauterine infection, preterm labor, neonatal sepsis, and asphyxia if not properly managed. This case study aims to describe the application of Evidence Based Practice (EBP) in midwifery care for a woman in labor with PROM at Al-Fatah General Hospital Ambon. The case involved Mrs. D, a 22-year-old woman, G2P1A0, at 34 weeks of gestation, who was admitted to the hospital with complaints of watery discharge from the birth canal accompanied by lower abdominal pain and blood-stained mucus. Examination revealed cervical dilation of 7 cm, absence of membranes, fetal head at Hodge III, and a fetal heart rate of 145 beats per minute. The diagnosis was established as intrapartum stage I active phase with preterm premature rupture of membranes (PPROM). Midwifery management included close observation of labor progress, administration of Ringer’s Lactate infusion, and prophylactic intravenous Cefotaxime according to WHO guidelines. After four hours without progress, collaboration was carried out with an obstetrician, and a cesarean section (SC) was performed due to inadequate labor progression and risk of intrauterine infection. The implementation of EBP in this case proved to enhance maternal and neonatal safety through rapid, rational, and collaborative clinical decision-making. This evidence-based approach reflects Al-Fatah General Hospital Ambon’s commitment to providing safe, effective, and high-quality midwifery care.